Peranan Filsafat Ilmu Terhadap Pendidikan - Abdul Muhid (Prodi Ilmu Administrasi Negara, 2016)
The aim of this research is to know the Philosophy Science and Education. The kind of the research is Library one in Samarinda. The human and philosophy have correlation with a life closely. The human has mind and many needs to fulfill the want which bears the philosophy thinking. The results of the research are (1). The philosophy is not only the play of the mindset but also has a function in the human living. (2). Philosophy is the matter scientiarium which has born may. The suggestions are To face many phenomenas the human is claimed to be sensitive to the development of the era so he or she have to have intellectual towards them.